Christmas effect on global stock markets / Muhd Isyah Na'im Abdul Karim - Abdul Karim, Muhd Isyah Na'im (2017)
Christmas holiday effect is an important holiday events impacting the behaviour or investors, asset prices, and financial market behaviours globally. Christmas event which is celebrated on every 25th December of the year is the number one religious holidays celebrated with a great enthusiasm by the Christian community around the globe. The significant important of this holidays is supported with the fact that Christmas holiday is one of the most celebrated religious holiday in the world by largest population of Christian community located in various geographical continents.